Embolization of a congenital arteriovenous fistula of the internal maxillary artery: A case report and review of the literature. Issue 3 (June 2016) - Santillan, Alejandro; Johnson, Jeremiah; Birnbaum, Lee A
A 13 year-old girl with a congenital carotid–jugular fistula presented with a pulsatile mass and a thrill on the left side of her neck. Angiography showed a fistula between the left internal maxillary artery and the jugular vein. The patient underwent coil embolization using a transarterial balloon-assisted technique and one week later, a transvenous approach. The fistula was completely obliterated, and the patient's symptoms resolved.